Fossil Subduction Zone Beneath the Eastern Yangtze Craton: Evidence From Seismic Reflections in the Upper Mantle - Xiaofan Deng; Qin Wang; Shaoping Lu; Haiyan Wang; Zhanwu Lu; Xiaoyu Guo; Hongqiang Li; Rui Gao (Geophysical Research Letters)
Abstract The Yangtze Craton in South China is generally regarded as an Archean‐Paleoproterozoic continental nucleus with a coherent basement that collided with the Cathaysia Block in the Early Neoproterozoic. Here we reprocessed a 300‐km‐long NW‐trending seismic reflection profile in the eastern Yangtze Craton. High amplitude events reveal the nearly flat Moho at depth of ∼40 km and SE‐dipping mantle reflections extending from ∼54 km to at least 100 km beneath the eastern Sichuan fold‐and‐thrust belt. We interpret these mantle reflections as a fossil subduction zone within the eastern Yangtze Craton, which was probably linked with a buried Paleoproterozoic orogen beneath the Xuefengshan belt. Hence the Yangtze Craton should be formed by the collision or accretion of microcontinents prior to the Neoproterozoic. During NW‐ward crustal shortening in the Middle Jurassic, this mantle suture zone controlled the thick‐to thin‐skinned structural transition from east to west due to tectonic inheritance.